P300/CBP inhibition sensitizes mantle cell lymphoma to PI3Kδ inhibitor idelalisib - Zhou Xiao-ru; Li Xiao; Liao Li-ping; Han Jie; Huang Jing; Li Jia-cheng; Tao Hong-ru; Fan Shi-jie; Chen Zhi-feng; Li Qi; Chen Shi-jie; Ding Hong; et al. (Acta Pharmacologica Sinica, 2022)
Mantle cell lymphoma (MCL) is a lymphoproliferative disorder lacking reliable therapies. PI3K pathway contributes to the pathogenesis of MCL, serving as a potential target. However, idelalisib, an FDA-approved drug targeting PI3Kδ, has shown intrinsic resistance in MCL treatment. Here we report that a p300/CBP inhibitor, A-485, could overcome resistance to idelalisib in MCL cells in vitro and in vivo. A-485 was discovered in a combinational drug screening from an epigenetic compound library containing 45 small molecule modulators. We found that A-485, the highly selective catalytic inhibitor of p300 and CBP, was the most potent compound that enhanced the sensitivity of MCL cell line Z-138 to idelalisib. Combination of A-485 and idelalisib remarkably decreased the viability of three MCL cell lines tested. Co-treatment with A-485 and idelalisib in Maver-1 and Z-138 MCL cell xenograft mice for 3 weeks dramatically suppressed the tumor growth by reversing the unsustained inhibition in PI3K downstream signaling. We further demonstrated that p300/CBP inhibition decreased histone acetylation at RTKs gene promoters and reduced transcriptional upregulation of RTKs, thereby inhibiting the downstream persistent activation of MAPK/ERK signaling, which also contributed to the pathogenesis of MCL. Therefore, additional inhibition of p300/CBP blocked MAPK/ERK signaling, which rendered maintaining activation to PI3K-mTOR downstream signals p-S6 and p-4E-BP1, thus leading to suppression of cell growth and tumor progression and eliminating the intrinsic resistance to idelalisib ultimately. Our results provide a promising combination therapy for MCL and highlight the potential use of epigenetic inhibitors targeting p300/CBP to reverse drug resistance in tumor.